Understanding financialization: Standing on the shoulders of Minsky - Charles Joseph Whalen (Levy Economics Institute of Bard College, 2017)
Since the death of Hyman Minsky in 1996, much has been written about financialization. This paper explores the issues that Minsky examined in the last decade of his life and considers their relationship to that financialization literature. Part I addresses Minsky's penetrating observations regarding what he called money manager capitalism. Part II outlines the powerful analytical framework that Minsky used to organize his thinking and that we can use to extend his work. Part III shows how Minsky's observations and framework represent a major contribution to the study of financialization. Part IV highlights two keys to Minsky's success: his treatment of economics as a grand adventure and his willingness to step beyond the world of theory. Part V concludes by providing a short recap, acknowledging formidable challenges facing scholars with a Minsky perspective, and calling attention to the glimmer of hope that offers a way forward.
Keywords: B31; B52; G00; 330; Hyman Minsky; money manager capitalism; financialization